Sophia: Local Trust for Securing Routing in DHTs - Gracia-Tinedo, R.; García-López, P.; Sanchez-Artigas, M. (2011 11th IEEE/ACM International Symposium on Cluster, Cloud and Grid Computing, 2011)
Distributed Hash Tables (DHTs) have been used as a common building block in many distributed applications, including Cloud and Grid. However, there are still important security vulnerabilities that hinder their adoption in today's large-scale computing platforms. For instance, routing vulnerabilities have been a subject of intensive research but existing solutions rely on redundancy in lieu of improving the quality of routing paths. In this paper, we present Sophia, a novel generic security technique which combines iterative routing with local trust to fortify routing in DHTs. Sophia strictly benefits from first-hand observations about the success/failure of a node's own lookups to improve forwarding paths. Moreover, unlike redundant routing, Sophia dynamically protects routing without introducing additional network overhead. To the best of our knowledge, this is the first work which exploits a local trust system to fortify routing in DHTs. We compared the performance of Sophia with redundant routing in Kademlia DHT. We obtained significant improvements regarding routing resilience, self-adjustment and network traffic reduction.